USING QUALITY OF SERVICE VIRTUAL PRIVATE NETWORK (VPN) ON E-KTP BANDAR LAMPUNG - Novi Herawadi Sudibyo; Muhammad Said Hasibuan (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Implementation e-ktp in Bandar Lampung , there areseveral obstaclesin the field, among others, areoftendelays inthe exchange of databetween theserverthatislocatedin the districtandthat is inthe centralserver. Tofindthe cause ofthese obstaclesand the importance ofthequality ofnetwork servicesit is necessarytodothemeasurementthatcanbeusedtomeasurethePerformance of/qualityofnetworkservice VPN that isused in theimplementation of E-Ktpin Bandar Lampungon each -eachin the district, the main problemin this studyis"Identification of QualityofService Virtual PrivateNetwork (vpn) on the Implementationof Electronic-Ktp"in Bandar Lampung. By using Axcent Net Toolsandmethods used action research model with QoSmonitoringsystem.KEYWORDS: Network VPN, Quality Of Service,ActionResearch